TRUST AND BEHAVIORAL INTENTION AS PREDICTORS OF FINANCIAL TECHNOLOGY ADOPTION - Muhammad Fathur Ramadhan Siagian; Hafiza Adlina (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Advances in digital technology have changed people's transaction patterns, including the use of digital payment systems in Medan City. QRIS Dana as one of the leading digital wallets offers practical and efficient transaction convenience. The trust factor and user intention are important aspects that influence the actual use of this service. This phenomenon shows that users are increasingly influenced by trust and behavioural intention factors in their decision to use QRIS Dana. This research seeks to investigate the impact of trust and behavioural intention on the real-world usage of QRIS Dana in Medan City. The research methodology employed is quantitative, using an associative approach. The study population consists of individuals in Medan City who have utilised QRIS Dana, with a sample size of 100 participants chosen through purposive sampling. Primary data collection involved distributing surveys, while secondary data was gathered through literature review. The examination techniques employed consist of validation testing, consistency testing, traditional assumption testing, multiple linear regression, partial testing, simultaneous testing, and determination testing. The findings indicated that confidence (X1) and intention (X2) towards behaviour have a partial and simultaneous impact on the genuine adoption (Y) of QRIS Dana. In accordance with the determination test coefficient, the correlation between trust (X1) and intention (X2) towards behaviour on actual adoption (Y) has an R value of 0.861. As per the adjusted R square value, it is evident that trust and intention contribute 73.5% towards genuine adoption, while the remaining 26.5% is influenced by other unspecified variables.